Andean permafrost in taluses and block- slopes in the Agua Negra Basin, Argentina – Detection and Distribution - Ortiz, Diana A. (2023)
The periglacial belt of the Dry Andes of Argentina (17°30’S to 35°S) is characterized by the development of several cryogenic landforms (Schrott, 1998; Trombotto et al., 1997), many of which have been so far underestimated -in terms of spatial distribution, internal structure and hydrological significance-. Rock glaciers are among the most studied landforms (Halla et al., 2021, Blöthe et al., 2021) even though they cover less than 2% of the surface in this sector of the Andes. Taluses and block-slopes are hardly studied, although they are widespread. Geomorphological mapping and statistical modeling of taluses and block-slopes are conducted for the very first time in the Agua Negra catchment (ca. 30°S and 69°W) and show a coverage of approximately 82% for the upper part of the catchment. This work presents first insights on existence, distribution and internal structure of permafrost in taluses, protalus ramparts and block-slopes in the Agua Negra catchment using a geophysical approach. A combination of systematic two-dimensional measurements of Electrical Resistivity Tomography (ERT), Seismic Refraction Tomography (SRT) and Ground Penetrating Radar (GPR) were conducted. Results show a presence of permafrost within taluses and protalus ramparts, with differences in their distribution and ice-rich/ ice-poor permafrost bodies. The geophysical data will be used to estimate the volume of ice and water content using the Four Phase Modelling approach.